MicroRNA‐762 promotes breast cancer cell proliferation and invasion by targeting IRF7 expression. (2nd November 2015) - Li, Yongping; Huang, Ruixue; Wang, Ling; Hao, Junsheng; Zhang, Qiong; Ling, Rui; Yun, Jun
Abstract: Objectives: miRNAs play crucial roles in human tumourigenesis. This study was performed to measure expression and function of miR‐762 in breast cancer. Materials and methods: Expression of miR‐762 in breast tissues and cell lines (SK‐BR‐3, DA‐MB‐435s, MCF‐7 and MDA‐MB‐231, HBL‐100) was measured by using real‐time RT‐PCR. We restored expression of miR‐762 in MCF‐7 cells to measure its functional roles. Luciferase assays were performed to reveal the target gene of miR‐762. Results: Expression of miR‐762 was high in both breast cancer cell lines and specimens, and its overexpression increased breast cancer cell proliferation and invasion. Interferon regulatory factor 7 (IRF7) is a direct target of miR‐762 and overexpression of miR‐762 reduced expression of IRF7. Moreover, IRF7 was repressed, its levels inversely correlated to miR‐762 expression. IRF7 rescued miR‐762‐induced cell invasion and proliferation. Conclusions: These results demonstrate that miR‐762 tumour effect was achieved by targeting IRF7 in human breast cancer specimens.